EFFECT OFF EXTRINSIC CUES ON PERCEPTION OF PRIVATE LABEL QUALITY. THE MODERATING ROLE OF STORE IMAGE - Nikhil Varghese (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Extrinsic and Intrinsic cues (E-CUE and I-CUE) are used by customers to not only make purchasing decisions but develop perception about a brand or a set of brands in terms of quality. A retail store sells two kinds of brands in terms of ownership. i.e. national brands (NB) and private labels (PLB). The perception of quality of NBs is not a prerogative (through the retailers aids in branding a bit through retail store level) of a specific retailer as it is owned and marketed by a national level company. But a retailer can do anything with PLBs as he owns them. So perception towards private labels be it quality or anything else is is in the hands of retailer itself. Retailers are interested in PLBs as their margins on PLBs are far higher than NBs. So if a retailer is able to have a desired combination of PLBs and NBs so that his overall profitability may go up. But this is only possible if the retailer knows about the level of perception of service quality towards PLBs. So this paper attempt to explore how E-CUEs affect the perception of private label service quality. Paper also attempts to measure the moderating role of store image as an E-CUE in the relationship between E-CUE and PL quality.